Optimum Design of Novel UWB Multilayer Microstrip Hairpin Filters with Harmonic Suppression and Impedance Matching - Homayoon Oraizi; Nima Azadi-Tinat (International Journal of Antennas and Propagation)
Optimum design of a novel ultra-wideband multilayer microstrip hairpin filter is presented, providing for harmonic suppression and impedance matching between source and load impedances. The theory of N-coupled transmission lines is employed to obtain an equivalent circuit for development of a design procedure based on the method of least squares. A prototype model of proposed two-layer filter of order 5 is fabricated for 3.1–10.6 GHz. The dimensions of designed filter are 23 mm × 7 mm. The insertion loss in the passband varies from 0.3 dB to 3 dB (in the worst case at the edge of passband) and in the stopband is about 30 dB up to 20 GHz. Its group delay in the UWB region is about 0.5 ns. Close agreement among the filter frequency responses as obtained by the proposed method, full-wave computer simulation softwares, and measurement data verify the effectiveness of the proposed filter structure and design methods.